Information communication technologies for human services education and delivery concepts and cases - Martin, Jennifer, 1959-; Hawkins, Linette (Information Science Reference, 2010)
"This book covers main areas of education and practice of disciplines engaged in the human services, includeing policy, community work, community education, field education/ professional practicum, health promotion, individual and family work"--Provided by publisher.